Comparison of Development and Antioxidative Ability in Fertilized Crossbred (Yorkshire × Landrace × Duroc) Oocytes Using Duroc and Landrace Sperm - Hayoung Lee; Hyewon Kim; Jisoon An; Hee-Tae Cheong; Sang-Hee Lee (Animals)
Pig production through crossbreeding methods is a pillar of the swine industry; however, research on the fertilization ability of male pigs in crossbreeds is lacking. Therefore, this study investigated the effects of Duroc sperm (DS) and Landrace sperm (LS) on fertility in Yorkshire × Landrace × Duroc (YLD) oocytes. Sperm were collected from the Duroc and Landrace species, and sperm characteristics, viability, and acrosome reactions were analyzed using flow cytometry. Oocytes were collected from YLD ovaries, and the fertility of DS and LS was determined using in vitro fertilization (IVF). Reactive oxygen species (ROS) and antioxidative abilities were analyzed using H2DCFDA and a Cell Tracker Red assay. Pluripotency (OCT4, SOX2, and NANOG), antioxidative (SOD1, SOD2, CAT, and GPx1), apoptotic (Bax and Bcl-2), and cell cycle-related (Cdc2 and CCNB1) genes were detected using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in oocytes fertilized with sperm. The results showed no significant difference in viability or acrosome reaction between DS and LS. ROS levels were significantly lower in the LS group than in the DS group, whereas glutathione (GSH) levels in the embryo did not significantly differ between the DS and LS groups. The OCT4, GPx1, and Cdc2 mRNA expression levels were significantly higher in the LS than DS groups. Blastocyst formation was significantly higher in the LS than DS groups. ROS levels were reduced, and blastocyte formation was increased in LS-obtained embryos. In conclusion, these results provide a fundamental understanding of using Landrace semen in the three-way crossbreeding of YLD pigs.